The National Foreclosure Mitigation Counseling Program (NFMC) and Spanish-Speaking Immigrants: A Case Study. Issue 5 (18th September 2020) - Rodriguez, Maria Y.
ABSTRACT: The National Foreclosure Mitigation Counseling Program was a consumer-level response to the 2008 foreclosure crisis. Evaluations of the NFMC argued its effectiveness across groups, yet little work has addressed its effectiveness in communities navigating structural barriers to housing market participation, such as recent immigration and language preferences. Using administrative data collected between 2007 and 2013, as well as in-depth interviews with foreclosure-mitigation counselors, this case study examines the implementation of the NFMC in a predominantly Spanish-speaking, immigrant community. Results indicate foreclosure-counseling outcomes were strongly associated with factors related to recent immigration and language preference.